Elaboración de ladrillos ecológicos a base de Politileno para la Empresa Fudesma del cantón Latacunga, Provincia de Cotopaxi en el periodo Abril 2017 - Febrero 2018. - Reinoso Tapia, Erika Lucero (2018)
In this work the ecological brick type Lego with a dimension of 300 x 150 x 85 mm was elaborated based on recycled polyethylene, cangahua, cement and water. It was carried out by means of an electrohydraulic pressing at 200 psi; a curing process was applied irrigating it 2 times daily for 7 days. The results obtained are cheaper bricks for the construction of houses, have a weight of 10 lb. and a resistance of compression 3.81 MPa. Its innovative design of Lego type that streamlines the work, this type of brick does not require the cooking process, which reduces pollution. The relevant aspect of the ecological brick is that it consists of a construction material that is friendly to the environment since cooking is not used in the manufacturing process, as is done in the process of traditional bricks that the kilns emit pollutant gases and soot, affecting the ecosystem and the health of the human being. Its innovative design allows the construction of an easy and quick way for the master bricklayer saving time and complications. The studies carried out in the laboratories of the National Polytechnic School indicate that this brick has a greater mechanical resistance 25, 33% to the traditional bricks being feasible for its use and commercialization. For the characterization of each combination proposed in each phase of the ecological bricks of (cangahua with PET, puzolana, traditional burned), the simple compression resistance test, the bending test and the humidity test have been carried out. In addition, a follow-up of the weight losses that occur during the curing time of the brick was carried out after 7 days. This brick type Lego in addition to a good appearance responds to ecological and sustainable criteria because it requires a low level of energy for its manufacture.